Pengaruh Kebijakan Moneter Terhadap Inflasi Periode Pra dan Selama Pademi Covid-19 - Gema Adi Wibisana (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
This study aims to find the effect of monetary policy on inflation through the bank lending channel. This research uses path analysis as a research method with dummy variables to show differences before the pandemic and during the pandemic. The study shows that monetary policy in influencing inflation needs to be through intermediate or intervening variables, especially before the pandemic, namely through PUAB variables, credit interest rates and bank reserves. Research also shows that PUAB and interest rates significantly affect inflation, while bank reserves do not. During the pandemic period, only the PUAB had a significant effect on inflation.